(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Thixotropic properties of Latvian Devonian and Quaternary clays were studied. Dynamic viscosity of the water clay suspensions were measured with a rotating viscometer. Influence of concentration, pH and modifiers on the thixotropic clay properties was analyzed. It was found that Latvian clays have thixotropic properties. Stability of clay suspensions is described with the thixotropy hysteresis loop. Increasing the speed of the viscometer rotation, dynamic viscosity of the clay suspension decreases. It was found that the solid phase concentration and mineralogical composition make an impact on the thixotropy of clays. Decreasing the solid phase concentration in the clay suspensions from 50% to 25%, dynamic viscosity decreases proportionally to the solid phase concentration. It was found that modifying clay suspensions with carboxymethyl cellulose (0,1g) increases concentration of structure forming. In the same time, modifying of clay suspensions with calcified soda (0,1g) decreases the structure forming concentration. Dependence of pH value from the solid phase concentration slightly decreases with the clay phase concentration increasing in the suspension.